2007
DOI: 10.1002/chem.200601086
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Insights into Stereoselective Catalysis—The Effects of Counterions in a CuII–Bissulfoximine‐Catalyzed Diels–Alder Reaction

Abstract: The initial steps of an enantioselective Diels-Alder reaction catalyzed by a CuII-bissulfoximine complex were followed by EXAFS (EXAFS=extended X-ray absorption fine structure), EPR (EPR=electron paramagnetic resonance) spectroscopy (CW-EPR, FID-detected EPR, pulse ENDOR, HYSCORE; CW=continuous wave; ENDOR=electron nuclear double resonance; HYSCORE=hyperfine sublevel correlation; FID=free induction decay), and UV-visible spectroscopy. The complexes formed between the parent CuX2 (X=Cl-, Br-, TfO-, SbF6-) salts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…Bolm et al, 32,33 previously reported the influence of the counterion and choice of starting metal salt for Diels-Alder reactions using the structurally similar Cu II bis(sulfoximine) complexes. The EPR spectra of the copper-bissulfoximine complexes showed significant differences depending on the starting Cu IIsalt (CuCl 2 , CuBr 2 , Cu(OTf ) 2 and CuCl 2 -AgSbF 6 ).…”
Section: Role Of the Counterion In Cu II Box Complexesmentioning
confidence: 99%
See 1 more Smart Citation
“…Bolm et al, 32,33 previously reported the influence of the counterion and choice of starting metal salt for Diels-Alder reactions using the structurally similar Cu II bis(sulfoximine) complexes. The EPR spectra of the copper-bissulfoximine complexes showed significant differences depending on the starting Cu IIsalt (CuCl 2 , CuBr 2 , Cu(OTf ) 2 and CuCl 2 -AgSbF 6 ).…”
Section: Role Of the Counterion In Cu II Box Complexesmentioning
confidence: 99%
“…One of the first groups to recognise how advanced EPR techniques can be used to probe these counterion (TfO − , SbF 6 − , Cl − , Br − ) effects for the related Cu IIbissulfoximine complexes in the Diels-Alder reaction was Bolm and Gescheidt. 32,33 Therefore in the current investigation we describe the detailed characterisation of the paramagnetic Cu II BOX complexes (shown in Scheme 1) using EPR and ENDOR spectroscopy, with specific emphasis on the influence of the counterion (TfO − or Cl − ) on the structure of the complex in solution.…”
Section: Introductionmentioning
confidence: 99%
“…42,43 For Cu(II) bis(sulfoximine) complexes, we have shown that penta coordination occurs in the course of (hetero) Diels-Alder reactions, with counterions and solvent molecules participating in the first coordination sphere. 44,45 A compatible geometry was found by X-ray analysis in the complex [Cu(II)t-Bu(box)(OH 2 ) 2 ](OTf ) 2 . 10 The question is whether such an arrangement of ligands ( penta-coordination) represents a general concept within the course of Cu(II) catalyzed Diels-Alder reactions.…”
Section: Introductionmentioning
confidence: 57%
“…Interestingly, these two salts gave opposite enantiomers (Entries 11 and 12) with copper being superior in terms of enantioselectivity (41 % ee). [d] Cu(BF 4 ) 2 71 23 17 [d] Cu(PF 6 ) 2 79 0 18 [d] Cu(SbF 6 ) 2 93 6 19 [d] Cu (ClO 4 ) In previous studies it was shown that counterions are involved in the resulting sulfoximine-copper(II) complex, [25] and consequently their effect on the given catalysis (yielding 9a from 7a) was also studied in this work. Entries 12-19 of Table 3 reveal that their influence on both yield and enantioselectivity was significant with noncoordinating anions such as perchlorate, tetrafluoroborate, and triflate being the best.…”
Section: Resultsmentioning
confidence: 88%